Environmental pollutants and the obesity: proven causalities and open questions - Ćurčić, Marijana; Esteban, Javier; Cakmak, Gonca; Durgo, Ksenija; Baralić, Katarina; Živanović, Jovana; Marić, Djurdjica; Buha Đorđević, Aleksandra; Antonijević Miljaković, Evica; Bulat, Zorica; Antonijević, Biljana; Djukić Ćosić, Danijela (Archives of Pharmacy, 2024)
The link between environmental pollution and obesity is of high importance, because understanding the relationship between the two can provide valuable insights into the complex factors contributing to the obesity epidemic. These chemicals, termed “obesogens,” are believed to disrupt lipid metabolism processes, therefore promoting the development of obesity. Human activities such as industrialization, urbanization, agriculture, and transportation have significantly contributed to environmental pollution. Therefore, the main identified obesogens are BPA found in plastics, food packaging, and thermal paper receipts, phthalates, commonly used in plastics, personal care products, and food packaging, toxic metal(oid)s, determined in non-stick cookware, water-resistant fabrics, and food packaging, pesticides, used in agriculture, as well as other persistent organic pollutants (POPs), and pharmaceuticals (waste). Addressing environmental pollution not only has the potential to improve environmental quality, but also to promote public health and prevent obesity-related diseases. Addressing the causality between pollutants and obesity could be a new and challenging road map for health professionals.